2009
DOI: 10.1164/rccm.200811-1730oc
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Epithelial–Mesenchymal Transition in Primary Airway Epithelial Cells from Patients with Asthma by Transforming Growth Factor-β1

Abstract: TGF-beta1 induces EMT in a Smad3-dependent manner in primary AECs. However, in asthmatic-derived ALI-AEC cultures, the number of cells undergoing EMT is greater. These findings support the hypothesis that epithelial repair in asthmatic airways is dysregulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
298
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(334 citation statements)
references
References 57 publications
(71 reference statements)
25
298
1
2
Order By: Relevance
“…It has been considered that the loss of the epithelial marker E-cadherin and the induction of the mesenchymal marker N-cadherin are fundamental events in EMT. 25 BEAS-2B cells exposed to 10 ng/ml TGF-b up to 72 h induced a change of morphology consistent with EMT and cellular N-cadherin (brown staining, Figure 2a). When 1-20 mM kaempferol was added to epithelial cells in the presence of TGF-b, the EMT process was disturbed with concurrent diminution of cellular N-cadherin induction (Figure 2a).…”
Section: Suppression Of Lps-and Ova-triggered Induction Of Tgf-b1 By mentioning
confidence: 85%
“…It has been considered that the loss of the epithelial marker E-cadherin and the induction of the mesenchymal marker N-cadherin are fundamental events in EMT. 25 BEAS-2B cells exposed to 10 ng/ml TGF-b up to 72 h induced a change of morphology consistent with EMT and cellular N-cadherin (brown staining, Figure 2a). When 1-20 mM kaempferol was added to epithelial cells in the presence of TGF-b, the EMT process was disturbed with concurrent diminution of cellular N-cadherin induction (Figure 2a).…”
Section: Suppression Of Lps-and Ova-triggered Induction Of Tgf-b1 By mentioning
confidence: 85%
“…In contrast, we found that AGE inhibited TGF-β-induced ERK1/2 and SMAD2 phosphorylation, and increased SMAD7 expression, which was suppressed by TGF-β. TGF-β induces the alveolar EMT in human lung epithelial cells via a SMAD2-or SMAD3-dependent pathway (Yao et al, 2004;Kasai et al, 2005;Hackett et al, 2009) and is considered to be an important step toward fibroblastic foci formation in IPF (Thannickal et al, 2004;Gharaee-Kermani et al, 2007). SMAD7 inhibits TGF-β signaling through competitive binding to type 1 receptors, and it inhibits the activation of SMAD2/3 (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMP2, BMP4 and BMP7 induce a mesenchymal-like morphology in normal primary airway epithelial cells (AECs) and enhance the rate of cell migration and increase α-SMA protein expression in AECs during restitution of a disrupted epithelium [3]. Others have also shown that TGF-β1 induces EMT in primary AECs and that EMT may be enhanced in asthmatic airways [80,81]. These findings lead us to hypothesise that BMP signalling is a key initiator of airway epithelial cell migration after injury and that the migration process involves a transient EMT-like phase.…”
Section: Bmp Emt and Tissue Regenerationmentioning
confidence: 99%